2021
DOI: 10.3390/ma14102601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization and Thermodynamic Analysis of Laser-Polished Landscape Design Products Using 3D Printing

Abstract: Recent innovations in 3D printing technologies and processes have influenced how landscape products are designed, built, and developed. In landscape architecture, reduced-size models are 3D-printed to replicate full-size structures. However, high surface roughness usually occurs on the surfaces of such 3D-printed components, which requires additional post-treatment. In this work, we develop a new type of landscape design structure based on the fused deposition modeling (FDM) technique and present a laser polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Laser polishing had shown significant improvement in the surface properties of FFF parts. [131][132][133] The key process variable that impacts the surface quality is laser power. The laser power and beam size of 3 W and 200 μm respectively are the optimal process conditions for the FFF PLA specimen.…”
Section: Hot Air Jettingmentioning
confidence: 99%
“…Laser polishing had shown significant improvement in the surface properties of FFF parts. [131][132][133] The key process variable that impacts the surface quality is laser power. The laser power and beam size of 3 W and 200 μm respectively are the optimal process conditions for the FFF PLA specimen.…”
Section: Hot Air Jettingmentioning
confidence: 99%
“…They suggested that laser polishing would be a useful technique for smoothing the surfaces of FDM parts. Ba et al (2021) showed the surface roughness of the laser-polished PLA FDM surfaces was reduced from over Ra 15 µm to less than 0.25 µm. Kumbhar and Mulay (2016) studied the improvement of surface roughness of ABS FDM parts using a CO 2 laser, and the results show that the value was reduced from Ra 4.2484 µm to 0.228 µm.…”
Section: Use Of Lasersmentioning
confidence: 98%